Pelatihan Pembuatan Kerajinan Tangan Aksesoris manik – manik dan Pemasaran Digital Melalui Aplikasi Tiktok: Inovasi Kreatif dan Peluang Bisnis di Era Digital - Anggita Cindy Fironika; Lisafi Kulbi; Arsa Karendra; Ariel Lintang Maulita (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The creative industry in Indonesia has experienced rapid growth in recent years, causing increasingly tight trade competition and various innovations in product marketing. This research focuses on the handicraft industry, especially accessories such as bracelets, necklaces and rings. Even though stringing looks easy, the biggest challenge is creating a unique design and ensuring the strength of the connecting rope so that it doesn't come loose easily. As technology develops, handicraft producers are now utilizing digital marketing to expand their market reach. Digital marketing, which involves the use of social media for promotion, has become a key strategy in the industry. This research specifically highlights the use of the social media platform TikTok as a digital marketing tool. TikTok, which is popular among teenagers and young adults, provides e-commerce features such as TikTok Shop and live shop, which allow manufacturers to sell their products directly through the app. Through this research, we explore the effectiveness of TikTok as a digital marketing medium for handicraft producers, as well as how this platform can support the growth of the creative industry in Indonesia.